"Tattooing in the Age of Instagram". Issue 4 (3rd April 2022) - Ryan Force, William
ABSTRACT: This article explores the impact of Instagram on tattoo culture. The role of this technology is considered from the perspective of tattoo artists, whose work has been transformed by social media. Using interviews, participant observation, and qualitative content analysis, the author outlines the rapidly developing changes to tattooing ushered in by social media like Instagram. New social media technology has not only altered the long-standing practices of tattoo artists (like the construction of portfolios, the display of flash, and advertising) but resulted in the emergence of a distinct tattoo scene with associated cultural styles and new working practices. This scene engages tattooing's deviant past alongside its increased acceptability as an art form. Ultimately, the use of social media like Instagram has not only elevated the visibility of tattoos as a cultural phenomenon but reshaped the work of tattooists.